2015
DOI: 10.1063/1.4935488
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic model of force-free current sheets with non-uniform temperature

Abstract: go.warwick.ac.uk/lib-publicationsOriginal citation: Kolotkov, D. Y., Vasko, I. Y. and Nakariakov, V. M.. (2015) Kinetic model of force-free current sheets with non-uniform temperature. Physics of Plasmas, 22 (11). 112902. Permanent WRAP URL:http://wrap.warwick.ac.uk/78634 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(57 citation statements)
references
References 53 publications
6
51
0
Order By: Relevance
“…In fact it seems to be a feature generally observed that for pressure tensors (that correspond to force-free fields) constructed in this manner (Harrison & Neukirch 2009a;Wilson & Neukirch 2011;Abraham-Shrauner 2013;Kolotkov et al 2015) the plasma-β is necessarily bounded below by unity. In a recent paper, Allanson et al (2015) used the pressure transformation techniques described above, resulting in a pressure tensor of 'multiplicative form'…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact it seems to be a feature generally observed that for pressure tensors (that correspond to force-free fields) constructed in this manner (Harrison & Neukirch 2009a;Wilson & Neukirch 2011;Abraham-Shrauner 2013;Kolotkov et al 2015) the plasma-β is necessarily bounded below by unity. In a recent paper, Allanson et al (2015) used the pressure transformation techniques described above, resulting in a pressure tensor of 'multiplicative form'…”
Section: 2mentioning
confidence: 99%
“…In particular, forcefree current sheets are relevant for the solar corona (Priest & Forbes 2000), Jupiter's magnetotail (Artemyev, Vasko & Kasahara 2014), the Earth's magnetotail Petrukovich et al 2015) and the Earth's magnetopause (Panov et al 2011). Further relevant theoretical works on distribution functions (DFs) for (nonlinear) forcefree current sheets are, for example, Harrison & Neukirch (2009a,b), Neukirch, Wilson & Harrison (2009), Wilson & Neukirch (2011), Abraham-Shrauner (2013), Allanson et al (2015) and Kolotkov, Vasko & Nakariakov (2015).…”
Section: O Allanson T Neukirch S Troscheit and F Wilsonmentioning
confidence: 99%
See 1 more Smart Citation
“…The first solution for a nonlinear force-free field was found by Harrison and Neukirch 38 (see also Ref. 39) for the force-free Harris sheet, and these solutions were later extended by Kolotkov et al 2 to allow for non-uniform density and temperature profiles (with respect to the spatial coordinate). A number of other equilibrium DFs have also been found for this field.…”
Section: Introductionmentioning
confidence: 99%
“…The DFs discussed give rise to spatially uniform temperature and density profiles, in a similar way to some of the models mentioned above. In this paper, we will extend this class of DFs to include those consistent with non-uniform temperature and density profiles, using a similar approach used by Kolotkov et al 2 for the force-free Harris sheet. As for AbrahamShrauner's DFs, the new DFs we will discuss include both the linear force-free limit and the force-free Harris sheet limit.…”
Section: Introductionmentioning
confidence: 99%